Research on the state of blended learning among college students – A mixed-method approach - Deng, Chao; Peng, Jiao; Li, ShuFei (Frontiers in Psychology, 2022)
The technology acceptance and participation of students in blended learning determine the effect of learning. In the wake of the COVID-19 pandemic in 2019, China's education leaders began to focus on and promote blended learning. Blended learning is still in its infancy in Chinese universities. The development of blended learning is a problem to be solved in colleges and universities. Combining technology acceptance and student participation, this paper proposes a learning influencing factor analysis model to analyze the influencing factors of blended learning. Questionnaires were distributed and designed, and 796 valid questionnaires were collected. The mean and variance were used to analyze the status of students' technology acceptance and satisfaction with blended learning. The t test method is used to analyze the gender differences of students in blended learning. The results show that :(1) students majoring in computer science have a high level of influence factors on blended learning. (2) There are significant differences in service quality between male and female computer major students. There is no significant difference in perceived usefulness, perceived ease of use and computer self-efficacy between male and female computer majors. (3) There are significant differences in skill involvement and participation of computer major college students. Based on these findings, this paper provides theoretical and practical suggestions for the implementation of blended learning to improve the effect of blended learning.